The BET inhibitor/degrader ARV-825 prolongs the growth arrest response to Fulvestrant + Palbociclib and suppresses proliferative recovery in ER-positive breast cancer - Finnegan, Ryan M.; Elshazly, Ahmed M.; Patel, Nipa H.; Tyutyunyk-Massey, Liliya; Tran, Tammy H.; Kumarasamy, Vishnu; Knudsen, Erik S.; Gewirtz, David A. (Frontiers in Oncology, 2023)
Anti-estrogens or aromatase inhibitors in combination with cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors are the current standard of care for estrogen receptor-positive (ER+) Her-2 negative metastatic breast cancer. Although these combination therapies prolong progression-free survival compared to endocrine therapy alone, the growth-arrested state of residual tumor cells is clearly transient. Tumor cells that escape what might be considered a dormant or quiescent state and regain proliferative capacity often acquire resistance to further therapies. Our studies are based upon the observation that breast tumor cells arrested by Fulvestrant + Palbociclib enter into states of both autophagy and senescence from which a subpopulation ultimately escapes, potentially contributing to recurrent disease. Autophagy inhibition utilizing pharmacologic or genetic approaches only moderately enhanced the response to Fulvestrant + Palbociclib in ER+ MCF-7 breast tumor cells, slightly delaying proliferative recovery. In contrast, the BET inhibitor/degrader, ARV-825, prolonged the growth arrested state in both p53 wild type MCF-7 cells and p53 mutant T-47 D cells and significantly delayed proliferative recovery. In addition, ARV-825 added after the Fulvestrant + Palbociclib combination promoted apoptosis in WT and RB deficient MCF-7 cells. These studies indicate that administration of BET inhibitors/degraders, which are currently being investigated in multiple clinical trials, may potentially improve standard of care therapy in metastatic ER+ breast cancer patients and may further prolong progression-free survival.